FACTORS RELATED TO THE INCIDENCE OF DIARRHEA IN TODDLERS IN THE WORK AREA OF UPTD PUSKESMAS TANJUNG AGUNG - Yustina Oktarida; Roni Ferdi; Sari, Diva Maudi Putri Naisyah (Majalah Kedokteran Sriwijaya, 2025)
Diarrheal disease is a major cause of child mortality and morbidity in the world, and is mostly the result of contaminated food and water sources. To identify the variables linked to the prevalence of diarrhea in young children in the Tanjung Agung Health Center UPTD’s service area. Correlation analysis and cross-sectional approaches are used in this analytical observational study. All 267 mothers with toddlers made up the study’s population. Random sampling was used to choose the study’s sample, which included up to 100 toddlers with diarrhea. utilizing a questionnaire to obtain data. Data collection using a questionnaire. Based on the results of the study, the application of No Given Exclusive Breastfeeding 62.5%, No Washing Hands Using Soap 47.4%, Work 22.2%. The results of the analysis of Factors Related to the Incidence of Diarrhea in Toddlers Exclusive Breastfeeding with a value of p = 0.006. Factors that are not related to the Incidence of Diarrhea in Toddlers are, Washing Hands Using Soap p = 0.686, and Occupation p = 0.317. There are Exclusive Breastfeeding with the incidence of diarrhea among toddlers. Additionally, hand soap use and occupation are unrelated factors to the prevalence of diarrhea in toddlers.